DETERMINATION OF NICKEL AND CHROMIUM IN PINUS NIGRA L., CEDRUS LIBANI, AND CUPRESSUS ARIZONICA LEAVES TO MONITOR THE EFFECTS OF POLLUTION IN ELAZIG (TURKEY) - Karaaslan, Nagihan M.; Yaman, Mehmet (Taylor & Francis Inc, 2013)
The aim of this article is to determine the air quality and to monitor the effects of pollution in Elazig, Turkey using plants. For this purpose, nickel (Ni) and chromium (Cr) concentrations in three plant species were determined. The leaves of the Pinus nigra L., Cedrus libani, and Cupressus arizonica together with soil samples were collected from different points depending on traffic intensity, proximity to the city center and cement factory, as well as control locations during different months of the year. Flame atomic absorption spectrophotometry (FAAS) was used for measurement of the metals in clear digests after the dry ashing method. Nickel and Cr concentrations were in the range from
Keywords: air pollution; biomonitor; Cedrus libani; Cupressus arizonica; Pinus nigra L; trace metals